Orthodox Religious Art of South Albania from the 16th to the 19th Centuries - Rozela Dhimgjini (Pharos Journal of Theology)
The present study aimed to investigate the peculiarities of the evolution of Orthodox religious art in South Albania in the 16th-19th centuries. The basis for the analysis was the iconographic and technological aspects of the exhibits from the collection of the Museum of Medieval Art in Korçë. The results of the study identified four main stages in the development of local Orthodox art – from Onufry’s workshop to the work of the Chetiri family. The study determined that walnut wood was used in 63% of iconographic works, and two-layer plaster with the addition of organic fibres served as the basis for the works. The study of temple paintings demonstrated the transformation of Byzantine canons, which were supplemented by regional elements, both in the modelling of forms and in decorative decoration. The study of monastery archives made it possible to trace the structured system of training painters, which involved the gradual mastery of techniques and the heredity of skills. The study of the architectural characteristics of the churches revealed a close relationship between the building forms and the concept of paintings. The active use of local building materials and the introduction of technical solutions for the preservation of wall paintings were identified. The study identified the main stages of the development of Orthodox art in the region, revealed technological and artistic features, and established the mechanisms of interaction between different artistic traditions in the formation of the local school of church painting.